New complex hyperbolic and trigonometric solutions for the generalized conformable fractional Gardner equation - Rezazadeh, Hadi; Kumar, Dipankar; Sulaiman, Tukur Abdulkadir; Bulut, Hasan (World Scientific Publ Co Pte Ltd, 2019)
This study focuses on acquiring new complex hyperbolic and trigonometric function solutions to the generalized conformable fractional Gardner equation by using two distinct integration schemes, namely: the modified Kudryashov method and the hyperbolic function method with the help of symbolic computation package. We generate new closed-form solitary wave solutions to the governing model. Implemented schemes are pragmatically effective for solving various types of nonlinear partial differential equations with integer or fractional order arising in various fields of applied sciences.
Keywords: Conformable fractional derivative; the general fractional Gardner equation; modified Kudryashov method; hyperbolic function method; new closed-form solutions